The effects of intermittent fasting on cardiovascular health of Prediabetes and Type 2 Diabetes Mellitus (T2DM) patients: a systematic review - Afdzal Rasif, Muhammad Naif Hafizin; Nazri, Amirah Farhana; Soe, May Khin (2023)
Diabetes mellitus is the one of the chronic diseases that has hig prevalence worldwide In 2021, there are 537 million (10.3%) adults living with diabetes worldwide and this number is predicted to increase to 643 million by 2030.bIDF in their recent research reported that 352 million adults between the age of 20 and 79 may have prediabetes. It is well established that patients with prediabetes and type 2 diabetes mellitus will commonly have a 2-3-fold increases risk of developing cardiovascular diseases. Intermittent fasting is one of the common approaches that is being practiced to reduce the daily calorie intake and as a form of dietary intervention to prevent and manage prediabetes and T2DM and their associated complications. There are many reported benefits of IF but there are no studies found that discuss specifically regarding the benefits of IF on cardiovascular system in T2DM patients.